2013
DOI: 10.1016/j.cbi.2013.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Donor substrate specificity of bovine kidney gamma-glutamyltransferase

Abstract: Mammalian γ-glutamyltransferase (GGT) is a glycoprotein consisting of two subunits -a light chain and a heavy chain. The light chain contains the catalytic activity; the heavy chain anchors the protein to the membrane. GGT catalyzes the hydrolysis of the γ-glutamyl isopeptide bond of glutathione conjugates, releasing glutamic acid, or the transfer of the γ-glutamyl group to an acceptor substrate. The specificity of the enzyme for xenobiotic donor substrates has not been

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…An investigation of the rates of transpeptidation of a series of donor GSH S-conjugates of aromatic compounds showed that the catalytic efficiency varied by a factor of four with bovine kidney GGT (Agblor and Josephy 2013). The GSH analog ophthalmic acid (L-c-Glu-L-a-aminobutyryl-Gly) and several S-substituted GSH analogs also serve as donor substrates for rat kidney GGT (Tate and Meister 1974a); GSSG and c-(DL-a-methylglutamyl)-L-Cys-Gly are poor donor substrates with Met as the acceptor.…”
Section: Transpeptidationmentioning
confidence: 99%
“…An investigation of the rates of transpeptidation of a series of donor GSH S-conjugates of aromatic compounds showed that the catalytic efficiency varied by a factor of four with bovine kidney GGT (Agblor and Josephy 2013). The GSH analog ophthalmic acid (L-c-Glu-L-a-aminobutyryl-Gly) and several S-substituted GSH analogs also serve as donor substrates for rat kidney GGT (Tate and Meister 1974a); GSSG and c-(DL-a-methylglutamyl)-L-Cys-Gly are poor donor substrates with Met as the acceptor.…”
Section: Transpeptidationmentioning
confidence: 99%
“…Because many sensitive methods are available for the accurate quantification of amino acids, as reviewed in [23], this approach would enable quantification of low concentrations of GSHconjugates provided that hydrolysis to glutamic acid and glycine is quantitative and that these amino acids are not further degraded under the conditions used. Hydrolysis of GSH-conjugates can be done non-enzymatically by acidic or alkaline hydrolysis [23] or using ␥-glutamyltranspeptidase and dipeptidases [24,25]. In the present study alkaline hydrolysis was applied followed by subsequently derivatization by o-phthaldialdehyde/N-acetylcysteine (OPA/NAC), a well-established and highly sensitive method for fluorimetric quantification of amino acids [23,26].…”
Section: Introductionmentioning
confidence: 99%